Thioglycosides in Carbohydrate Research. (11th February 2015) - Lian, Gaoyan; Zhang, Xiaheng; Yu, Biao
Graphical abstract: Highlights: The promoters for glycosidation of alkyl/aryl 1-thioglycosides are listed. Representative examples for the application of thioglycosides are highlighted. The advantages and disadvantages of thioglycosides as donors are commented. Abstract: The promoters that have been developed for the glycosidation of alkyl/aryl 1-thioglycosides, the applications of thioglycosides in the synthesis of glycans and glycoconjugates, and the advantages and disadvantages of thioglycosides as donors in the syntheses are reviewed briefly, with examples being selected, to a large extent, from those published in Carbohydrate Research .